Implementation of Tai-Type Cooperative Learning to Increase Students' Mathematical Representation Based on The Constructivist Approach - Nasruddin, Nasruddin; Mashuri, Sufri; Djidu, Hasan; Jahring, Jahring (Journal of World Science, 2023)
This study aims to determine the average increase in the mathematical representation ability of students who are taught using Team Assisted Individualization (TAI) learning and conventional learning and to see the effectiveness of the TAI learning model with a constructivist approach. The subjects in this study were students of class VIII SMP Negeri 3 Samaturu in the even semester. Sampling was carried out using cluster random sampling technique as the experimental unit selected two research classes. Data analysis techniques using descriptive statistics and inferential statistics. Furthermore, the results of inferential statistics on hypothesis testing using the t-test. Based on the results and discussion in this study, several conclusions were obtained, namely: (1) students' mathematical representation abilities before being taught by the TAI model with a constructivism approach consisting of 19 students showed an average of 14.08, with a standard deviation of 5.78615; (2) students' mathematical representation abilities after being taught using TAI learning with a constructivism approach show an average value of 58.72, with a standard deviation of 7.332761; and (3) Learning mathematics through the TAI learning model is more effective than conventional learning.